Uso de la tierra en una región en proceso de colonización. ¿Diversificación o especialización productiva? El caso de la Región Norte de Costa Rica (1900-1955) - Solórzano Vargas, William (Revista de historia., 2005)
This article is aimed, on the one hand, at pointing out the changes in agricultural productivity in a region undergoing a settlement process, as was the case of the northern region of Costa Rica; and on the other hand, at providing data at the regional level that will allow for subsequent comparative analyses that will help clarify the real scope of specialization or diversification of the Costa Rican agricultural activities.